Respuesta :

Answer:

7b + 3r

Step-by-step explanation:

given

(3b + 2r) + (4b + r) ← remove parenthesis

= 3b + 2r + 4b + r ← collect like terms

= (3b + 4b) + (2r + r)

= 7b + 3r

ItzTds

Answer:

[tex] \red{ \sf \: B) \: 7b + 3r}[/tex]

Step-by-step explanation:

Given expression,

→ (3b + 2r) + (4b + r)

Now we have to,

→ Simplify the given expression.

Let's simplify the expression,

→ (3b + 2r) + (4b + r)

→ 4b + 3b + 2r + r

→ (4 + 3)b + (2 + 1)r

→ 7b + 3r

Hence, the option (B) is correct.